2018
DOI: 10.1590/s0100-83582018360100130
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Control, and Decomposition of Irrigated Forage Species under Glyphosate Doses and Shading

Abstract: Light intensity available in growing environments may influence the susceptibility of plants to glyphosate and decomposition of their residues. This study aimed to assess the productivity, control, and decomposition of forage straw submitted to glyphosate doses and exposed to full sun and 50% shade. Two experiments were carried out, one for Piatã grass (Urochloa brizantha cv. Piatã) and other for Tanzania grass (Megathyrsus maximus cv. Tanzania). The experimental design was a randomized block design with strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…The higher sensitivity of U. brizantha and Meghatirsus maximus to glyphosate in an environment with 50% light restriction, compared to plants kept in full sun, was reported Brant et al (2018). The higher sensitivity to glyphosate by weeds grown in shaded environments, compared to plants kept in full sun, was also observed for Commelina benghalensis , Macroptilium atropurpureum (Costa et al, 2020), Cyperus rotundus , Merremia cissoides (Ferreira et al, 2022a), and for Euphorbia heterophylla (Ferreira et al, 2022b) corroborating what was found in the present study.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The higher sensitivity of U. brizantha and Meghatirsus maximus to glyphosate in an environment with 50% light restriction, compared to plants kept in full sun, was reported Brant et al (2018). The higher sensitivity to glyphosate by weeds grown in shaded environments, compared to plants kept in full sun, was also observed for Commelina benghalensis , Macroptilium atropurpureum (Costa et al, 2020), Cyperus rotundus , Merremia cissoides (Ferreira et al, 2022a), and for Euphorbia heterophylla (Ferreira et al, 2022b) corroborating what was found in the present study.…”
Section: Discussionmentioning
confidence: 72%
“…Research, Society and Development, v. 11, n. 17, e177111738758, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10. 33448/rsd-v11i17.38758 This research study innovates in relation to Brant et al (2018) for testing intermittent shading in simulation of what happens in field conditions with shading by other larger species. Studies on the response of plants to light restriction use the shade of trees in cultivation environments (Santos et al, 2017), or artificial shading with sombrite (Parissi and Koukoura, 2009;Martins et al, 2014, Costa et al, 2020, Brant et al 2018, Ferreira et al, 2022a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A decomposição rápida da palhada de algumas espécies pode colocar o solo a uma exposição por maior tempo, ainda mais, quando as regiões apresentam condições edafoclimáticas como temperatura, luminosidade, clima e pluviosidade, acelerando esse processo. Sendo assim, recomenda-se a aplicação de espécies que tenham uma taxa de decomposição mais lenta, que por consequente aumentará a eficiência da cobertura do solo (BRANT et al;.…”
Section: Introductionunclassified